An assessment of gender vulnerability in the humanitarian crisis in Cox's Bazar, Bangladesh: Developing a gender-based vulnerability index in the Rohingya and Host community contexts. (15th October 2022) - Nasar, Sameen; Raz, Saifa; Parray, Ateeb Ahmad; Hossain, Muhammad Riaz; Sultana, Rafia; Nadim, A.S.M.; Jabbar, Abdul; Aktar, Bachera; Rashid, Sabina Faiz; Rahman, M Shafiqur
Abstract: The massive influx of Rohingya refugees in Cox's Bazar district of Bangladesh has created a severe humanitarian crisis, which has been exacerbated by the COVID–19 pandemic. The research focused on the most vulnerable groups (MVGs) of Rohingya and adjacent host communities, such as pregnant and/or lactating women, elderly people (64+ years), persons with disabilities (PWD), single female household heads, and adolescents, with the aim to assess the vulnerability among the MVGs and between the households in both communities by developing a gender-based vulnerability index (GBVI), using data from a cross-sectional study in selected Rohingya camps and surrounding host communities. The GBVI―developed as a linear combination of several indicators under nine different themes reflecting vulnerabilities in humanitarian crises―was used to classify the households of both communities into three levels of vulnerability: low (bottom 33.33%), medium (middle 33.33%) and acute (upper 33.33%). Findings show the intensity of vulnerability is significantly greater among the Rohingya households than those in the host community; almost 65% of Rohingya households were 'acutely vulnerable' compared to 2% of host households. In both communities, female-headed households (including single female) are found to be more vulnerable (the highest percentage of households with acute vulnerability), followed by households with elderly and PWDs. Further analysis suggests that households with acute vulnerability in both communities are deprived of receiving certain services, such as COVID–19 monetary support and disability allowances. It is recommended to identify acutely vulnerable households consisting of MVGs from both communities, understand their needs, and implement urgent policies/interventions.